LYOPHILIZED INJECTION: A MODERN APPROACH OF INJECTABLE DOSAGE FORM - Sheena, U; Parthiban, KG; Selvakumar, R (Journal of Drug Delivery and Therapeutics, 2018)
Now-a-days, lyophilized injection dosage form is extensively used to improve the bioavailability, stability, solubility and patient compliance. The lyophilized injection has considered as alternative to oral solid dosage forms for better patient compliance especially in bed ridden patients and for attaining maximum bioavailability, improved stability. The lyophilized injection reconstitute before injection to produce liquid injection. This review includes a detailed updated concept on lyophilized injection.Keywords: Lyophilized injection, parenteral, freeze drying